The Self-Worth of Cleaning Service Workers at One of Universities in Surabaya - Aqila Carinda Naura; Nurchayati Nurchayati (Universitas Negeri Surabaya, 2023)
This qualitative psychological research aims to identify and understand the self-worth of cleaning service workers at one of universities in Surabaya. This research is important to conduct considering the limited scope of similar research topics carried out by previous researchers. This study will provide a clear understanding of the self-worth possessed by cleaning service workers. Data was collected through interviews with three cleaners at this university who served as research participants. The Interpretative Phenomenological Analysis performed on the resulting data revealed individual differences in self-worth dynamics among the three cleaning service workers. In the performance aspect, two of them possessed a positive self-image. In the aspect of ability, all the three cleaning service workers displayed the same profiles. In the effort aspect, only one cleaning service worker exhibited it. In conclusion, one cleaning service worker had better self-worth than the other two. In addition, the research discovered that social support and moral standards served as protective factors, while appearances and social interaction operated as risk factors.